Effect of Combined Foot Bath and Foot Massage Therapy on Blood Pressure in Hypertensive Patients at Tambakrejo Health Center, Surabaya - Naharil Mumtazah; Minarti; Sari Lutfiyah; Mohammad Najib (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Hypertension, often referred to as a